2013
DOI: 10.1002/pssc.201300293
|View full text |Cite
|
Sign up to set email alerts
|

Current conduction mechanisms and breakdown fields of AlxTiyO/n‐GaAs(001) metal‐insulator‐semiconductor structures

Abstract: We investigated AlxTiyO/n‐GaAs(001) metal‐insulator‐semiconductor (MIS) structures, in which Alx TiyO thin films as high‐k dielectric were obtained by atomic layer deposition, utilizing alternative supply of Al2O3 and TiO2 precursors. Using X‐ray photoelectron spectroscopy, we obtained atomic composition ratios of Al and Ti in the Alx TiyO thin films. It is shown that the breakdown field of the AlxTiyO increases with increase in the Al composition.Based on temperature‐dependent current density‐voltage (J ‐V) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…52 Similar recent findings on nanolaminated Al x Ti y O on the III-V substrate by Ui et al show that upon increasing the barrier height Poole-Frenkel conduction changed to F-N tunneling for Al 2 O 3 . 53 Also Krylov et al clearly observed using X-ray photoemission spectroscopy and time of flight secondary ion mass spectrometry, the higher substrate diffusion process enhances the leakage current and reduces the break down voltage. 21 They have correlated their chemical and electrical analysis with the findings that leakage is enhanced by substrate out-diffusion.…”
Section: Resultsmentioning
confidence: 98%
“…52 Similar recent findings on nanolaminated Al x Ti y O on the III-V substrate by Ui et al show that upon increasing the barrier height Poole-Frenkel conduction changed to F-N tunneling for Al 2 O 3 . 53 Also Krylov et al clearly observed using X-ray photoemission spectroscopy and time of flight secondary ion mass spectrometry, the higher substrate diffusion process enhances the leakage current and reduces the break down voltage. 21 They have correlated their chemical and electrical analysis with the findings that leakage is enhanced by substrate out-diffusion.…”
Section: Resultsmentioning
confidence: 98%
“…2) One effective solution for balancing between κ and E G is employing aluminum titanium oxide [(Al 2 O 3 ) 1-x (TiO 2 ) x ] with intermediate properties of Al 2 O 3 (κ ∼ 9, E G ∼ 7 eV) and TiO 2 (κ ∼ 50, E G ∼ 3 eV). As a matter of fact, a high-quality Al 1-x Ti x O y gate insulator deposited by the atomic layer deposition (ALD) method and other vacuum deposition techniques has been used for Si-based, [3][4][5] GaAs-based 6,7) and GaN-based devices. 8,9) One alternative approach to obtain Al 1-x Ti x O y thin films is the mist chemical vapor deposition (mist-CVD) technique, which can deposit various metal-oxide thin films from relative non-toxic and nonpyrophoric aqueous solution under atmospheric pressure.…”
mentioning
confidence: 99%